Cover Feature: 2‐Acetamido‐2‐deoxy‐l‐iminosugar C‐Alkyl and C‐Aryl Glycosides: Synthesis and Glycosidase Inhibition (Eur. J. Org. Chem. 40/2018). Issue 40 (4th October 2018) - Fontelle, Nathalie; Yamamoto, Arisa; Arda, Ana; Jiménez‐Barbero, Jesús; Kato, Atsushi; Désiré, Jérôme; Blériot, Yves
Abstract : The Cover Feature shows the synthesis of unprecedented 2‐acetamido C ‐alkyl and C ‐aryl iminosugars. This synthesis was achieved through a Staudinger/aza‐Wittig/ Grignard/ring contraction sequence. An audacious parallel is made between Louis Blériot's achievement, being the first to fly an aircraft across the English Channel in 1909 and this work, the first "trip" to 2‐acetamido C ‐alkyl and C ‐aryl iminosugars, achieved by his relative and collaborators. The cover art was created by S. Riffaut. More information can be found in the Full Paper by Y. Blériot, A. Kato, J. Désiré et al.